COVID-19, A New Possible Mimicker of Interstitial Lung Disease Related to Primary Sjögren’s Syndrome - Alessia Laneri; Stefania Cerri; Giovanni Della Casa; Antonio Moretti; Andreina Manfredi; Marco Sebastiani; Enrico Clini; Carlo Salvarani (Case Reports in Medicine)
Introduction. Acute exacerbation of interstitial lung disease (ILD) and COVID-19 pneumonia show many similarities, but also COVID-19 sequelae, mainly when fibrotic features are present, can be difficult to distinguish from chronic ILD observed in connective tissue diseases. Case Report. In 2018, a 52-year-old woman, was diagnosed with primary Sjogren’s syndrome (pSS). The patient did not show respiratory symptoms, and a chest X-ray was normal. During March 2020, the patient was hospitalized for acute respiratory failure related to COVID-19 pneumonia. Three months later, follow-up chest high-resolution computed tomography (HRCT) showed ground glass opacity (GGO) and interlobular interstitial thickening. Pulmonary function tests (PFTs) showed slight restrictive deficit and mild reduction in diffusion lung of carbon monoxide (DLCO). The patient complained of asthenia and exertional dyspnoea. A multidisciplinary discussion including rheumatologist, pulmonologist, and thoracic radiologist did not allow a definitive differential diagnosis between COVID-19 persisting abnormalities and a previous or new-onset pSS-ILD. A “wait and see” approach was decided, monitoring clinical conditions, PFTs, and chest HRCT over time. Only 2 years after the hospitalization, improvement of clinical symptoms was reported; PFT also improved, and HRCT showed almost complete resolution of GGO and interlobular interstitial thickening, confirming the diagnostic hypothesis of long-COVID lung manifestations. Discussion. In the above-reported case report, 3 differential diagnoses were possible: a COVID-19-related ILD, a preexisting pSS-ILD, or a new-onset pSS-ILD triggered by COVID-19. Regardless of the diagnosis, the persistence of clinical and PFT alterations, suggested a chronic disease but, surprisingly, clinical and radiologic manifestations disappeared 2 years later.